Coronary to pulmonary fistula as the primary source of pulmonary blood supply in pulmonary atresia with ventricular septal defect (Medical Journal of Indonesia, 2004)
A communication between the coronary and pulmonary arteries, so called coronary to pulmonary fistula, is a rare source of pulmonary supply in pulmonary atresia (PA) with ventricular septal defect (VSD). A 4 year old girl referred to National Cardiovascular Center Harapan Kita, Jakarta with symptoms and signs of increased pulmonary blood flow since infancy and was confirmed by the chest x-rays. Heart examination revealed normal first heart sound with single loud second heart sound and an ejection systolic murmur at the pulmonary area. ECG demonstrated sinus rhythm with normal axis and biventricular hypertrophy. Echocardiography was performed and truncus arteriosus (TA) type I was suspected with perimembranus VSD, overriding of the aorta, and dilated main pulmonary artery. But on cardiac catheterization studies, a non obstructive fistula was found between the left coronary and main pulmonary artery coexisted with PA and VSD. A successful surgery was performed subsequently and confirmed the above diagnosis. Although there were episodes of pulmonary hypertension crisis during early post operative course, she was then discharge from the hospital in a good condition. Since irreversible pulmonary vascular disease may develop in a non restrictive coronary to pulmonary fistula, early recognition of this anomaly is very important for better surgical result. (Med J Indones 2004; 13: 237-40)